Building Competitive Rural Enterprises through Collaborative Governance: A Model for Strengthening BUMDes in Indonesia - Saputra, Robert; Havlicek, Tomas (International Journal of Economics, Business, and Entrepreneurship, 2025)
Village-Owned Enterprises (BUMDes) have emerged as key instruments for rural economic development in Indonesia, yet many face challenges in sustainability, innovation, and stakeholder engagement. This study proposes an integrated strategic model combining the Penta-Helix collaboration framework and value chain analysis to strengthen BUMDes performance. Drawing on qualitative case studies from three villages in Kepulauan Meranti Regency—Bina Maju, Semukut, and Tanjung—the research explores how collaboration with government, academia, private sector, media, and community aligns with value creation across enterprise stages. Data were collected through semi-structured interviews and analyzed thematically. Findings reveal strong community and government roles, but limited integration of academic, private, and media actors. The study identifies context-specific gaps and proposes a stakeholder-aligned implementation roadmap to improve BUMDes operations. This research contributes a flexible, scalable model for building competitive, collaborative, and resilient rural enterprises, offering both theoretical insight and practical guidance for local governments, development agencies, and BUMDes managers.